ANALISIS IMPLEMANTASI TATA KELOLA ADMINISTRASI GURU DAN TENAGA KEPENDIDIKAN BERBASIS DIGITAL PADA SD NEGERI 1 TAMBAHREJO - Agustina, Helinda (YHMM PUBLISHING, 2024)
This study aims to analyze the implementation of digital-based administrative governance for teachers and education personnel at SD Negeri 1 Tambahrejo. The research is motivated by the growing importance of digital transformation in educational administration systems to improve efficiency, transparency, and accountability in educational services. This study employs a qualitative approach, utilizing data collection techniques such as observation, in-depth interviews, and documentation. The findings reveal that the implementation of digital administrative systems at SD Negeri 1 Tambahrejo has had a positive impact on managing personnel data, attendance, and reporting processes. However, several challenges remain, including limited technological infrastructure, varying levels of digital literacy, and the need for continuous training for teachers and education staff. This study recommends strengthening technical support and enhancing human resource capacity as strategic steps to optimize digital-based administrative governance in primary schools.